Konversi Termal Kayu Akasia (Acacia Mangium) Menjadi Bio-Oil Dengan Teknologi Pirolisis Menggunakan Katalis Mo/NZA - Meliagustin, Adilla; Bahri, Syaiful; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Availability of petroleum fuels are increasingly limited. Limitations of petroleum fuels will not be balanced with the needs of the community will fuel increased day by day. To overcome these problems needed alternative energy sources that can be updated is one of the bio-oil. Bio-oil is produced from biomass with the pyrolysis process, in the absence of oxygen. The purpose of this research was the synthesis of bio-oil from akasia wood, determine the effect of the impregnation percentage of Mo metal and ratio of catalyst Mo/NZA on the yield of bio-oil and determine the physical and chemical characteristics of bio-oil. Pyrolysis using 50 grams acacia wood, 500 ml silinap and Mo/NZA catalyst with variations of the impregnation percentage of Mo metal 0%, 1%, 3% and 6%, and the variations ratio of catalyst Mo/NZA 3%, 6% and 9% of the biomass with a stirring speed of 300 rpm and a temperature of 320ÂºC for 120 minutes. In this research, the highest yield on the variation of the impregnation percentage of metal 3% and the ratio of catalyst 9% of the biomass amounted to 76,084%. Characteristics of bio-oil obtained were density 0,827 gr/ml, viscosity 2,032 cSt, acid number 88,677 mg NaOH /gr sample, and the flash point 43 oC. The results of GC-MS analysis, the dominant chemical components in the bio-oil were Cyclohexane (13,477%), 2,4-Hexadiene (2,610%), 6-Tridecene (1,920%), Propane (1,684%) and 4-Nonene (0,619 %).Keyword: Bio-oil, pyrolysis, catalyst Mo/NZA, akasia wood